Accuracy of a point-of-care major crossmatch test and risk factors for major crossmatch incompatibility in cats. (June 2021) - Blois, S.L.; Marshall, H.; Abrams-Ogg, A.C.G.; Bersenas, A.M.; Ruotsalo, K.; Monteith, G.
Highlights: Gel-based and enhanced laboratory crossmatching methods had poor agreement. Previous transfusion history increased risk of crossmatch incompatibility in cats. Further work is needed to standardize crossmatch methods in veterinary medicine. Abstract: Major crossmatch testing can help identify immunologic incompatibilities between blood donors and recipients; however, there are limited studies describing the accuracy of point-of-care crossmatch tests. The first aim of this study was to determine if a gel-based, point-of-care major crossmatch method (GEL-CM), without antiglobulin-enhancement, could accurately detect compatible and incompatible donor–recipient pairings, using an antiglobulin-enhanced laboratory-based major crossmatch method (LAB-CM) as the reference standard. The second aim was to describe the incidence of, and risk factors for, major crossmatch incompatibility in cats. Nineteen previously-transfused cats and 32 transfusion-naïve cats, representing 132 unique donor-recipient pairings, were included in this study. Both LAB-CM and GEL-CM tests were performed for most parings. There was poor agreement between the LAB-CM and GEL-CM results (kappa = 0.111; 95% confidence interval [CI], −0.093 to 0.314). Transfusion-naïve cats had incompatibility rates of 3% and 6% using LAB-CM and GEL-CM, respectively; previously-transfused cats had incompatibility rates of 32% and 26% using LAB-CM and GEL-CM, respectively. History of previous transfusion was the only identified cat risk factor for an incompatible LAB-CM (odds ratio [OR], 31.0; 95% CI, 3.77–254.98; P = 0.0019) and GEL-CM (OR, 5.7; 95% CI, 1.72–19.20; P = 0.0054). Further studies are needed to determine if GEL-CM can detect clinically-relevant immunologic incompatibilities that would result in transfusion reactions. Major crossmatch testing is of greater importance in cats that have previously received a transfusion.